Pengaruh Berbagai Larutan Perendaman Terhadap Vase Life pada Tiga Jenis Bunga Potong Krisan - Sisca, Pebria; Anrya Darma, Wika; Tiara, Dede (J-Plantasimbiosa, 2025)
Chrysanthemum flowers still have a limited shelf life (vase life) after harvest, which is greatly influenced by various internal and external factors. This study aims to obtain the effect of various soaking solutions (aquadest, sugar, Vitamin C, and lime) that are most effective on the vase life or freshness period of cut chrysanthemums and obtain differences in vase life responses between three types of chrysanthemums (purple, yellow, and white) to the solution treatment. This study used an experimental design, namely a randomized block design with two factors 3 x 4 and repeated 4 times. The research data were analyzed by ANOVA and tested BNJ test at a significance level of 5%. The results showed that the effective solution in the soaking solution used Vitamin C and lime which affected the observation of freshness scores, freshness duration, flower diameter and absorbed solution. Meanwhile, the types of cut chrysanthemums that had the best response were purple and yellow chrysanthemums.